Associations between knowledge, beliefs, and self-efficacy with COVID-19 preventive behavior in Denpasar, Bali Province - Rosita, Ni Putu Indah; Wirawan, I Made Ady; Kadek Tresna Adhi (Public Health and Preventive Medicine Archive, 2023)
Background and purpose: Positive cases of COVID-19 in Bali have been growing rapidly during the pandemic. Denpasar City has contributed almost one-third of all cases with a high incidence of local transmission. Preventive action is pivotal to halt transmission; thus, this study aims to determine the association between knowledge, belief, and self-efficacy with COVID-19 preventive behavior in the Denpasar, Bali Province community. Methods: This cross-sectional study was conducted in Denpasar City, Bali. The study involved 1040 respondents with an age range of 18-59 years. Data collected include sociodemographic characteristics, knowledge and perception on COVID-19 and preventive behaviour. Online questionnaires in Google form format were distributed via WhatsApp groups from February to March 2021. Data obtained were analyzed using the Chi-Square test followed by Logistic Regression. Results: The respondents' mean (SD) age was 35 years (4.98), and 52.7% were male. The education level was considered high, with the majority finishing Senior High School/College (99.2%), and most were working or holding a job (94.4%). Factors that were significantly associated with COVID-19 prevention behavior in Denpasar City were knowledge about COVID-19 (AOR=2.43; 95%CI: 1.70-3.48), a belief in susceptibility to COVID-19 (AOR=4.03; 95%CI: 2.34-6.94), a belief in the seriousness of the disease (AOR=2.91; 95%CI: 1.84-4.60), a belief in the benefits of prevention (AOR=8.38; 95%CI: 4.37–16.06), and self-efficacy (AOR=2.10; 95%CI: 1.45-3.05). Conclusion: Knowledge, belief, and self-efficacy are associated with COVID-19 preventive behavior in the community of Denpasar City. Awareness campaign is important to ensure adequate knowledge level attained especially for such a new emerging disease.